Penetapan kadar flavonoid ekstrak metanol kulit kayu raru (Cotylelobium lanceolatum Craib) pada variasi konsentrasi pelarut menggunakan metode spektrofotometri UV-Vis - Nasution, Kartika Zsaskia; Daulay, Anny Sartika; Ridwanto, Ridwanto; Nasution, Haris Munandar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The use of plant-based traditional medicine remains a common practice in developing countries, with more than 80% of the population relying on it for healthcare and treatment. In Indonesia, natural medicines continue to be a primary choice for public health, aligning with local traditions and cultural practices. One such medicinal plant is raru bark, which possesses various pharmacological activities, including antidiabetic, astringent, antilaxative, antibacterial, antiseptic, antidiarrheal, and blood-clotting properties. This study aims to characterize the methanol extract of raru bark and determine its flavonoid content using UV-Vis spectrophotometry. The research stages included plant material processing, methanol extraction, characterization tests, macroscopic and microscopic examinations, phytochemical screening, and flavonoid quantification. Phytochemical analysis revealed that the methanol extract of raru bark contains flavonoids, tannins, saponins, and triterpenoids. Characterization tests showed that all evaluated parameters met the required standards. Flavonoid quantification was performed by determining the maximum wavelength of quercetin using UV-Vis spectrophotometry at different solvent concentrations. The results indicated that the total flavonoid content at a 96% solvent concentration was 1.625 ± 0.153 mgQE/g, at 70% was 1.318 ± 0.003 mgQE/g, and at 50% was 1.146 ± 0.006 mgQE/g.